Modelo de Heisenberg para cadeia de spins - Oliveira, Ravenna Rodrigues (2016)
Everyday new technological inventions arrives in the world, improving the life of the society as one. For new devices to have improvements, science needs to be improved too. Within science, a subject that stands out is the magnetism properties of the materials, like ferromagnetic materials. Due to the studies about the magnetism properties of the materials become possible the criation of computer hard drive. In this dissertation, we use the Heisenberg model to better understand the spin waves, which commonly appear in magnetic materials. This model considers the exchange interation of spins, together with the Zeeman effect. In this dissertation we use the eisenberg model for spin waves applied to some networks. The study for a two layer network where one of them is displaced in relation to the other was done. The behavior for a network displaced to the left and a network equally dislocated to the right is the same. Due to the helical structure of an RNA molecule we study the Heisenberg model in a network around a cylinder. For this network, we found that case where the network is symmetrically displaced is degenerate, which can be broke by changing the network configuration, so there is no symmetry in the system.